Movimientos sociales rurales colombianos: de la resistencia a una cultura política alternativa en un mundo transnacional - Juan Pablo Bohorquez; Dermot O’Connor (Suma de Negocios, 2012)
Through a series of transformations, Colombian rural social movements have articulated a development project and a way of life which stand as alternatives to the imposition of neoliberal ideology on a transnational scale. This article presents a review of the literature on agrarian social movements and an analysis based on interviews with activists from four agrarian organizations: the National Association of Peasant Land Users – Unity and Reconstruction (ANUC-UR), the Federation of United Agricultural Trade Unions (Fensuagro-CUT), National Federation of Agricultural Cooperatives (Fenacoa) and the National Agrarian Coordinator (CNA) among others. This study examines the process through which these agrarian organizations have created an alternative political culture in domestic conditions of civil war. In addition, the article discusses the ongoing challenges facing these rural social movements at the present conjuncture.